1999
DOI: 10.1023/a:1008393226195
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive assessment of satisfaction with care: Preliminary psychometric analysis in an oncology institute in Italy

Abstract: Results of present psychometric testing of the CASC forecast adequate properties. This will be confirmed by repeating these analyses in a cross-cultural setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
64
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 17 publications
5
64
0
1
Order By: Relevance
“…Studies of cancer patients' evaluation of their stay in hospital generally conclude with high satisfaction rates (5,6,12), which is in agreement with our ndings. The published rate varies between 75% and 95%, and the variability is probably due to methodological differences.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Studies of cancer patients' evaluation of their stay in hospital generally conclude with high satisfaction rates (5,6,12), which is in agreement with our ndings. The published rate varies between 75% and 95%, and the variability is probably due to methodological differences.…”
Section: Discussionsupporting
confidence: 92%
“…The importance of physicians' and nurses' availability, their cooperative skills and human qualities as well as their technical competence are emphasized also in other studies (3 -5). Like Bredart et al (4,5), we found that adequate information given to the patients was highly related to 'patient satisfaction'. 'Adequate' information also includes the disclosure of an unfavourable prognosis, thus lowering 'unrealistic expectations'.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In our study too, various sources of information were listed by the respondents and misinformation has been demonstrated in the results. Bredart et al (1999) found that insufficient quality of health care provision may constitute an additional burden on patients. Besides, dissatisfaction with care may alter an already challenged compliance which in turn may undermine treatment effectiveness.…”
Section: Discussionmentioning
confidence: 99%